(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The study of air pollution is very important throughout the world. Among the biological methods the use of lichens as a bio-indicator has been very popular. Lichens are used as effective monitors to detect low-level air pollution which may affect different flora and fauna communities. Lichens have been widely recognized as effective eco-friendly bio-monitors for detection of metal deposition on trees, rocks and bare ground. This article is concerned with the use of lichens in bio-monitoring of air pollution, how the lichens do recognize air pollution, the mechanisms of accumulation and trapping of particulate matters, understanding the mechanisms of alterations and the methods of study and factors affecting the process. Species of various lichen like Lecanora, Candelariella, Dirinaria, Buelia, Laurera, Lecanora, can act as air pollution indicator.